The Effect of Brand Authenticity on Consumer Loyalty Through Brand Trust and Perceived Value for Apple Products Among Generation Z - Havid Han; Muhammad Raju; Sara (CV. Era Digital Nusantara, 2026)
This study addresses the problem of how premium technology brands maintain consumer loyalty among Generation Z, a segment that is increasingly critical of brand credibility, value alignment, and corporate authenticity. The objective of this study is to examine the effect of brand authenticity on consumer loyalty through the mediating roles of brand trust and perceived value in the context of Apple products. The method employed was quantitative with a descriptive design. Respondents were Generation Z Apple users residing in the Greater Jakarta area (Jabodetabek). The sample size was determined using the rule of five times the number of indicators, resulting in 205 respondents. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results of this study indicate that brand authenticity has a significant positive effect on perceived value (coefficient 0.705), brand trust (0.594), and consumer loyalty (0.277). Perceived value (0.475) and brand trust (0.226) also play important roles in strengthening consumer loyalty toward Apple products. The mediation analysis reveals that perceived value mediates the effect of brand authenticity on loyalty (0.335) more strongly than brand trust (0.134). These findings suggest that brand authenticity affects consumer loyalty both directly and indirectly through enhanced brand trust and perceived value. Therefore, strengthening brand authenticity may serve as an effective strategic approach for companies seeking to maintain consumer loyalty among Generation Z.